Benign hereditary chorea and deletions outside NKX2-1: What's the role of MBIP? - Invernizzi, Federica; Zorzi, Giovanna; Legati, Andrea; Coppola, Giovanni; d'Adamo, Pio; Nardocci, Nardo; Garavaglia, Barbara; Ghezzi, Daniele (Eur J Med Genet, 2018)
Heterozygous point mutations or deletions of the NKX2-1 gene cause benign hereditary chorea (BHC) or a various combinations of primary hypothyroidism, respiratory distress and neurological disorders. Deletions proximal to, but not encompassing, NKX2-1 have been described in few subjects with brain-lung-thyroid syndrome. We report on a three-generation Italian family, with 6 subjects presenting BHC and harboring a genomic deletion adjacent to NKX2-1 and including the gene MBIP, recently proposed to be relevant for the pathogenesis of brain-lung-thyroid syndrome. We observed a clear reduction of NKX2-1 transcript levels in fibroblasts from our patients compared to controls; this finding suggests that MBIP deletion affects NKX2-1 expression, mimicking haploinsufficiency caused by classical NKX2-1 related mutations.
Keywords: Cells, Cultured; Chorea; Haploinsufficiency; Humans; Intracellular Signaling Peptides and Proteins; Pedigree; Sequence Deletion; Thyroid Nuclear Factor 1